A Statistical Study of Longitudinal Extent of Pc1 Pulsations Using Seven PWING Ground Stations at Subauroral Latitudes. Issue 1 (17th January 2023) - Liu, Jie; Shiokawa, Kazuo; Oyama, Shin‐Ichiro; Otsuka, Yuichi; Jun, Chae‐Woo; Nosé, Masahito; Nagatsuma, Tsutomu; Sakaguchi, Kaori; Kadokura, Akira; Ozaki, Mitsunori; Connors, Martin; Baishev, Dmitry; et al.
Abstract: Pc1 geomagnetic pulsations correspond to electromagnetic ion cyclotron (EMIC) waves in the magnetosphere and are excited there with frequencies of 0.2–5 Hz. The instantaneous longitudinal extent of Pc1 waves on the ground has not been estimated yet. In this study, we analyze the Pc1 pulsations observed at seven longitudinally‐distributed ground stations at subauroral latitudes at ∼60° magnetic latitude for 1 year from July 2018 to June 2019. The hourly occurrence rates of Pc1 pulsations at all 7 stations have a peak (14%–39.6%) in the post‐noon sector and a local minimum (4.1%–8.1%) at midnight. The average frequencies become highest (0.6–1.1 Hz) after midnight and lowest (0.3–0.5 Hz) after noon at all 7 stations. An increasing tendency of total Pc1 occurrence with respect to magnetic latitude was observed. Based on these observations, we obtained a peak of probability distribution of the instantaneous Pc1 longitudinal extent as ∼82.5° with a half maximum at ∼114°, though this probability distribution can be affected by the limitation of the number of the stations. We also made model calculations on the possible longitudinal extent using artificial random Pc1 waves with fixed extents. The comparison of the model results with the observation suggests longitudinal extent of 70°–86° comparable to the peak of probability distribution (∼82.5°). A superposed epoch analysis shows that the longitudinal extent of Pc1 waves tends to increase during recovery phase of geomagnetic storms. Key Points: We study the longitudinal extent of Pc1 pulsations using 1 year of data obtained at seven ground stations at subauroral latitudes The occurrence rates of Pc1 pulsations at subauroral latitudes are highest in the post‐noon and lowest in the midnight sector The peak of probability distribution of the instantaneous Pc1 longitudinal extent is ∼82.5° with a half maximum at ∼114°